Efficacy and safety of Nuwiq® (human‐cl rhFVIII) in patients with severe haemophilia A undergoing surgical procedures. Issue 1 (19th October 2017) - Zozulya, N.; Kessler, C. M.; Klukowska, A.; von Depka, M.; Hampton, K.; Hay, C. R. M.; Jansen, M.; Bichler, J.; Knaub, S.; Rangarajan, S.
Abstract : Introduction: Haemophilia A patients are at a high risk of excess bleeding during surgeries. The aim of haemostatic therapy during the perioperative period is to normalize FVIII level perioperatively and postoperatively to maintain normal haemostasis until wound healing is complete. Aims/Methods: To examine the efficacy of Nuwiq ® (simoctocog alfa, human‐cl rhFVIII), a 4 th generation recombinant FVIII produced in a human cell line, for surgical prophylaxis in patients with severe haemophilia A. This analysis assessed the efficacy of Nuwiq ® during surgical procedures and in the postoperative period in seven clinical studies of previously treated patients (PTPs) with severe haemophilia A. Results: Thirty‐six patients, aged 3‐55 years, received surgical prophylaxis with Nuwiq ® for 60 surgeries (28 major and 32 minor). Efficacy was evaluated for 52 surgeries (25 major and 27 minor). The success rate of Nuwiq ® treatment was 98.1% (51 of 52 evaluated surgeries); haemostatic efficacy was assessed as "excellent" or "good" in all but one major surgery (assessed as "moderate"). The number of infusions ranged from 1 to 19 for minor surgeries and from 3 to 76 for major surgeries. The median (range) daily doses were 42.0 (28.2‐100.9) IU kg −1 for minor surgeries and 69.3 (43.3‐135.6) IU kg −1 for major surgeries. There were no serious treatment‐related adverse events, and none of the patients developed FVIII inhibitors. Conclusions: The results of this pooled analysis show that Nuwiq ® was efficacious in maintaining haemostasis during and after major and minor surgical procedures in PTPs with severe haemophilia A.